Antecedents of anger of medical workers in Singapore and the United States : a qualitative study of culture context and dyadic relationships - Ho, Adeline Li Sian (2008)
This research focuses on how various people from US and Singapore interact together and how this interaction leads to different antecedents of anger felt in each culture. A qualitative research method, involving in-depth interviews with employees from medical work setting representing both countries, was used.